Granice władztwa planistycznego przy uchwalaniu miejscowego planu zagospodarowania przestrzennego - Zwolak, Sławomir (Studia Prawa Publicznego, 2019)
The considerations of the article focus on the planning power exercised by a municipality as a unilateral and authoritative determination of the purpose of the land and its development. The municipality in the capacity of a planning authority cannot assume an absolute and unlimited power and must act within the limits determined by applicable and binding laws. Hence, in the implementation of its land development tasks, the municipality (or local authorities) are bound by the provisions of the Constitution of the Republic of Poland and other relevant laws that govern the planning authority granted to municipalities. Exceeding the limits of this planning power will occur when planning solutions prove to be arbitrary and lack substantive justification. Defective legal solutions include not only solutions that violate the law, but also those that result from a potential abuse of the competence of the municipality. Determining the land purpose and the manner of its management must reflect a reasonable and real need for the solution adopted. When the latter is detached from the legal and factual status of the land in question, a violation of planning power arises. When a municipality adopts a local plan which introduces certain restrictions in the use of the property right that is protected in the Constitution, it is obliged to apply legal measures that will be the least onerous for individual entities and which will remain in a rational proportion to the intended purposes. However, certain situations that will lead to the conflict of interests are unavoidable. Settling these conflicts in the process of law-making requires, each time, the weighing off the interests of individual property owners and the public interest of the whole local community. Individual owners may sue the municipal planning authority on the grounds of the abuse of its planning power when adopting a local land management plan and such legal actions may be effective.